High-strength, high-hardness and high-plasticity multi-component alloy material as well as preparation method and application thereof
By developing Al-Cu-Cr-Fe-Ti-V multi-component alloy material, adjusting Al content and optimizing phase structure, the shortcomings in strength, hardness and plasticity of existing paper cutter alloy materials are solved, and efficient and economical production is achieved, which is suitable for the shearing needs of papers of different hardness.
Patent Information
- Application Number
- CN202411871310.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-28
AI Technical Summary
The existing alloy materials for paper cutting knives have shortcomings in strength, hardness and plasticity, and require complex heat treatment processes, which are costly.
A multi-component alloy material of Al-Cu-Cr-Fe-Ti-V was developed. By adjusting the Al content, the phase structure of the alloy is optimized, and high strength, high hardness and good plasticity are achieved. It is prepared by a non-consumable vacuum arc smelting process to avoid heat treatment.
It achieves the significant improvement of the strength and plasticity of the alloy while maintaining high hardness, reduces production costs, and is suitable for the shearing needs of papers of different hardness.
Smart Images

Figure CN119710428A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-strength, high-hardness, and plastic multi-component alloy material and a preparation method and application thereof, belonging to the technical fields of alloy material technology and paper cutter technology. Background Art
[0002] At present, the alloy grades for paper cutters mainly include T10A, 9CrSi, W18Cr4V and so on. T10A is a common carbon tool steel with high hardness, good mechanical properties and easy processing, but low strength. It is mostly used to make medium and low-grade paper cutter blades. 9CrSi is a carbon steel material with high hardness and high wear resistance. It is often used to make medium and high-grade paper cutter blades. W18Cr4V is a high-speed steel with high hardness, high wear resistance and high heat resistance. It is suitable for paper cutter blades with high hardness requirements, but its brittleness is relatively large. The performance guarantee of the three alloys requires complex heat treatment processes, which is expensive. The traditional alloy system is mainly based on an element with certain special properties as the matrix, and a small amount of other elements is added to improve its performance. The types of commonly used metal elements are limited, and the amount of addition is also limited, which invisibly restricts the amount of alloy materials that can be used. Therefore, it is urgent to develop an alloy material that can meet high strength, high hardness and plasticity without heat treatment. Summary of the invention
[0003] The purpose of the present invention is to provide a high-strength, high-hardness, and plastic multi-component alloy material, and a preparation method and application thereof. The alloy material has ultra-high strength, hardness, and good plasticity. As an alloy for paper cutters, compared with existing alloys for paper cutters, the strength and plasticity are greatly improved while retaining high hardness.
[0004] In order to achieve the above object, the technical solution adopted by the present invention is:
[0005] A high-strength, high-hardness, and plastic multi-component alloy material, the composition of which is Al a Cu b Cr c Fe d Ti e V f , where a:b:c:d:e:f = (0.1-1.1):(0.8-1.2):(0.8-1.2):(0.8-1.2):(0.8-1.2):(0.8-1.2).
[0006] Preferably, the alloy material comprises Al 0.2 Cu1Cr1Fe1Ti1V1.
[0007] Preferably, the alloy material comprises Al 0.5Cu1Cr1Fe1Ti1V1.
[0008] Preferably, the composition of the alloy material is Al1Cu1Cr1Fe1Ti1V1 in atomic ratio.
[0009] The preparation method of any of the above-mentioned high-strength, high-hardness and plastic multi-component alloy materials is to place a metal titanium block and a metal element prepared according to a ratio in a non-consumable vacuum arc melting furnace respectively, and first melt the sponge titanium block under an inert atmosphere; evacuate the furnace, and arc melt the metal element under an inert atmosphere accompanied by electromagnetic stirring. After the arc melting is completed, the product is refining and repeated for multiple times to obtain an alloy sample; after removing the oxide layer on the surface of the alloy sample, it is melted and cooled to form.
[0010] Preferably, after the metal titanium block and the metal element are prepared, a step of removing impurities and oxides on the surface of the metal element and the metal titanium block is also performed, and the method for removing the oxide layer on the surface of the alloy sample is the same as the method for removing impurities and oxides on the surface of the metal element and the metal titanium block, specifically: using an angle grinder, a grinding wheel or sandpaper to grind the metal element, the metal titanium block, and the alloy sample, and then using alcohol or acetone as a cleaning solvent, the metal element, the metal titanium block, and the alloy sample are oscillated and cleaned in an ultrasonic wave for 3-20 minutes;
[0011] Among them, the power density of ultrasound is 0.5-1.5W / cm 2 , frequency is 20-100Hz.
[0012] Preferably, the purity of the metal element is ≥ 99.9 wt.%.
[0013] Preferably, the specific method of evacuating the air is to evacuate the air to 2.5×10 -3 After reaching 1-20 Pa, inert gas is added to restore the pressure in the furnace to 1-10 Pa.
[0014] Preferably, the arc melting current is 30-150A and the duration is 30-150s.
[0015] Preferably, the molding is carried out by vacuum suction casting with a pressure of 1-20Pa.
[0016] Application of any of the above-mentioned high-strength, high-hardness and plastic multi-component alloy materials in the preparation of paper cutters.
[0017] The beneficial effects of the present invention are:
[0018] The Al-Cu-Cr-Fe-Ti-V multi-component alloy system provided by the present invention achieves the best combination of strength, hardness and plasticity by adjusting the Al content to meet the shearing requirements of papers with different hardness. Its performance maintains the high hardness of existing paper cutter materials, and at the same time has obvious advantages over existing materials in terms of major performance indicators such as yield strength, breaking strength and breaking elongation. The obtained material is in a cast state and does not require heat treatment, thus saving a lot of heat treatment costs.
[0019] The alloy material has a simple two-phase and three-phase structure in the recast state, and has high strength, high hardness and plasticity. 0.5 CuCrFeTiV multi-component alloy has a three-phase structure of BCC+FCC+Laves in the cast state, with a yield strength of 1815MPa, a fracture strength of 2300MPa, a hardness of 60HRC, and an elongation of 18%. It has ultra-high strength, hardness, and good plasticity. Compared with the existing paper cutter materials, the strength and plasticity have been greatly improved while retaining high hardness. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the XRD spectrum of the Al-Cu-Cr-Fe-Ti-V ternary alloy system prepared in Examples 1, 2, and 3. DETAILED DESCRIPTION
[0021] The following embodiment provides a high-strength, high-hardness, and plastic multi-component alloy material for a paper cutter, wherein the composition is Al a Cu1Cr1Fe1Ti1V1, where a is 0.2, 0.5, and 1 respectively. When converted to atomic percentage, the corresponding calculation can be performed. When a=0.2, the atomic percentage of Al is (0.2 / 5.2)*100%, and the atomic percentages of the other elements are (1 / 5.2)*100%. When a=0.5 or 1, the calculation method of the atomic percentage of each element is the same as above.
[0022] Example 1
[0023] This embodiment provides a high-strength, high-hardness, and plastic multi-component alloy material for a paper cutter, comprising the following metal raw materials in an atomic ratio: Al 0.2, Cu 1, Cr 1, Fe 1, Ti 1, and V 1, expressed as Al 0.2 CuCrFeTiV multi-component alloy, referred to as Al 0.2 .
[0024] AboveAl 0.2 The preparation method of the multi-component alloy is as follows:
[0025] (1) Prepare metal ingots (single substance) of Al, Cu, Cr, Fe, Ti, V and titanium sponge blocks, and grind them with a grinder to remove surface impurities and oxides. The purity of each metal ingot is higher than 99.9wt%. After grinding, weigh them according to the proportion, and use acetone as the cleaning solvent. 2 The mixture was cleaned in an ultrasonic cleaning machine with a frequency of 33 Hz for 5 minutes and dried for later use;
[0026] (2) In a non-consumable vacuum arc melting furnace, a titanium sponge block is first melted in a Cu crucible under argon protection, allowing the titanium sponge to absorb the residual oxygen in the protective atmosphere to reduce the oxidation behavior during the melting of the multi-component alloy; then, weighed metal ingots are placed in another Cu crucible in order of melting point, and the vacuum is evacuated to 2.5×10 -3 After the temperature reaches 5 Pa, argon is backfilled to 5 Pa. Under the protection of argon, arc melting is performed at a current of 60 A to obtain a preliminary sample. During the arc melting process, electromagnetic stirring is accompanied to increase the uniformity of alloy mixing. The preliminary sample needs to be turned over (arc melted after turning over) for at least 5 times to obtain a button sample.
[0027] (3) Take out the button sample, remove its surface oxide layer, and then cut it into multiple samples, put it into the arc melting furnace and repeat step (2) (no additional refining is required), and then suck the liquid alloy into the mold at a pressure of 5 Pa to obtain Al 0.2 Multi-component alloy rods.
[0028] Example 2
[0029] This embodiment provides a high-strength, high-hardness, and plastic multi-component alloy material for a paper cutter, including metal raw materials with the following atomic ratios: Al 0.5, Cu 1, Cr 1, Fe 1, Ti 1, and V 1, expressed as Al 0.5 CuCrFeTiV multi-component alloy, referred to as Al 0.5 .
[0030] AboveAl 0.5 The preparation method of the multi-component alloy is as follows:
[0031] (1) Prepare metal ingots (single substance) of Al, Cu, Cr, Fe, Ti, V and titanium sponge blocks, and grind them with a grinder to remove surface impurities and oxides. The purity of each metal ingot is higher than 99.9wt%. After grinding, weigh them according to the proportion, and use acetone as the cleaning solvent. 2 The mixture was cleaned in an ultrasonic cleaning machine with a frequency of 33 Hz for 8 minutes and then dried for later use;
[0032] (2) In a non-consumable vacuum arc melting furnace, a titanium sponge block is first melted in a Cu crucible under argon protection, allowing the titanium sponge to absorb the residual oxygen in the protective atmosphere to reduce the oxidation behavior during the melting of the multi-component alloy; then, weighed metal ingots are placed in another Cu crucible in order of melting point, and the vacuum is evacuated to 2.5×10 -3 After the temperature reaches 5 Pa, argon is backfilled to 5Pa. Under the protection of argon, arc melting is performed at a current of 60A for 1.5min to obtain a preliminary sample. During the arc melting process, electromagnetic stirring is accompanied to increase the uniformity of alloy mixing. The preliminary sample needs to be turned over (arc melted after flipping) for at least 5 times to obtain a button sample.
[0033] (3) Take out the button sample, remove its surface oxide layer, and then cut it into multiple samples, put it into the arc melting furnace and repeat step (2) (no need to re-refine), and then suck the liquid alloy into the mold under a pressure of 8Pa to obtain Al 0.5 Multi-component alloy rods.
[0034] Example 3
[0035] This embodiment provides a high-strength, high-hardness, and plastic multi-component alloy material for a paper cutter, including metal raw materials Al 1, Cu 1, Cr 1, Fe 1, Ti 1, and V 1 in the following atomic ratios, expressed as A l CuCrFeTiV multi-component alloy, referred to as Al 1.0 .
[0036] AboveAl 1.0 The preparation method of the multi-component alloy is as follows:
[0037] (1) Prepare metal ingots (single substance) of Al, Cu, Cr, Fe, Ti, V and titanium sponge blocks, and grind them with a grinder to remove surface impurities and oxides. The purity of each metal ingot is higher than 99.9wt%. After grinding, weigh them according to the proportion, and use acetone as the cleaning solvent. 2 The mixture was cleaned in an ultrasonic cleaning machine with a frequency of 33 Hz for 10 min and dried for later use;
[0038] (2) In a non-consumable vacuum arc melting furnace, a titanium sponge block is first melted in a Cu crucible under argon protection, allowing the titanium sponge to absorb the residual oxygen in the protective atmosphere to reduce the oxidation behavior during the melting of the multi-component alloy; then, weighed metal ingots are placed in another Cu crucible in order of melting point, and the vacuum is evacuated to 2.5×10 -3 After the ingot is filled with argon to 5Pa, it is arc-melted for 1.5min at 60A under argon protection to obtain a preliminary sample. During the arc melting process, electromagnetic stirring is accompanied to increase the uniformity of alloy mixing. The preliminary sample ingot needs to be turned over (arc-melted after turning over) for at least 5 times to obtain a button sample.
[0039] (3) Take out the button sample, remove its surface oxide layer, and then cut it into multiple samples, put it into the arc melting furnace and repeat step (2) (no need to re-refine), and then suck the liquid alloy into the mold under a pressure of 10Pa to obtain Al 1.0 Multi-component alloy rods.
[0040] The Al2O3 of Examples 1 to 3 was analyzed by X-ray diffractometer. x Phase analysis of CuCrFeTiV (x=0.2, 0.5, 1) multi-component alloy was performed, the operating voltage and current were 40KV and 20mA respectively, the X-ray source was CuKα (λ=0.1542nm) ray, and the scanning angle 2θ ranged from 20 to 120°.
[0041] The XRD spectra of the alloys of Examples 1 to 3 are as follows: Figure 1 As shown by Figure 1 It can be seen that the phase structures of Al-Cu-Cr-Fe-Ti-V multi-component alloys with different Al contents are significantly different. Both Example 1 and Example 2 are composed of BCC+FCC+Laves phases, in which BCC has two phases, namely BCC and BCC'. The diffraction peak intensity of the Laves phase decreases with the increase of Al content. As the Al content further increases, the diffraction peak of the Laves phase disappears, and the phase structure of Example 3 changes from the original BCC+FCC+Laves phase to the BCC+FCC phase.
[0042] Three common alloys for paper cutters, T10A, 9CrSi, and W18Cr4V, were selected as comparative examples, and hardness tests and compression performance tests were performed on Examples 1 to 3 and Comparative Examples 1 to 3. The test data are shown in Table 1.
[0043] Among them, the hardness test method is: put the sample on the HR-150A digital microhardness tester, and measure the microhardness for 20 seconds on the cross section of the polished alloy sample with a 120° diamond cone indenter under a load of 150kgf. 10 points are measured on each sample, and the data are finally averaged.
[0044] Compression performance test method: The diameter of the cylindrical specimen used for the compression test is 4 mm and the height is 6 mm. The axis of the specimen is parallel to the outer surface of the cylinder, and the upper and lower planes are parallel. The compression test is carried out at room temperature using a computer-controlled high-temperature electronic universal testing machine. Apply 5.6×10 -3 A constant compression speed of mm / s corresponds to 10 -3 s -1 The initial strain rate.
[0045] Comparative Example 1: The alloy material used for the paper cutter is T10A.
[0046] The chemical composition of T10A is as follows:
[0047] Carbon (C): 0.95~1.04%
[0048] Silicon (Si): ≤0.35%
[0049] Manganese (Mn): ≤0.40%
[0050] Sulfur (S): ≤0.020%
[0051] Phosphorus (P): ≤0.030%
[0052] Chromium (Cr): Allowable residual content ≤ 0.25%
[0053] Nickel (Ni): allowable residual content ≤ 0.20%
[0054] Copper (Cu): allowable residual content ≤ 0.30%.
[0055] Comparative Example 2: The alloy material used for the paper cutter is 9CrSi.
[0056] The chemical composition of 9CrSi is as follows:
[0057] Carbon (C): 0.85~0.95%
[0058] Silicon (Si): 1.20-1.60%
[0059] Manganese (Mn): 0.30~0.60%
[0060] Sulfur (S): ≤0.030%
[0061] Phosphorus (P): ≤0.030%
[0062] Chromium (Cr): 0.95~1.25%
[0063] Nickel (Ni): allowable residual content ≤ 0.25%
[0064] Copper (Cu): allowable residual content ≤ 0.30.
[0065] Comparative Example 3: The alloy material used for the paper cutter is W18Cr4V. The chemical composition of W18Cr4V is as follows:
[0066] Carbon (C): 0.70~0.80%
[0067] Silicon (Si): 0.20~0.40%
[0068] Manganese (Mn): 0.10~0.40%
[0069] Sulfur (S): ≤0.030%
[0070] Phosphorus (P): ≤0.030%
[0071] Chromium (Cr): 3.80-4.40%
[0072] Nickel (Ni): allowable residual content ≤ 0.30%
[0073] Copper (Cu): allowable residual content ≤ 0.25%
[0074] Vanadium (V) 1.00~1.40%
[0075] Molybdenum (Mo): ≤0.30%
[0076] Tungsten (W): 17.50~19.00%.
[0077] Table 1 Performance data of Examples 1 to 3 and Comparative Examples 1 to 3
[0078]
[0079]
[0080] As can be seen from Table 1, the elongation at break of the alloy materials in Examples 1-3 increases with the increase of Al content. Example 3 can achieve a high plasticity of 37%, and at the same time is close to the three comparative examples in hardness, and the strength is greatly improved. The strength of the alloy materials in Examples 1 and 2 is further improved, but at the expense of a decrease in plasticity. Among them, the yield strength of Example 2 is 1815MPa, the plastic strain is 18%, and the hardness is 60HRC, which has the best combination of strength, hardness and plasticity. Its phase structure is a FCC phase with good plasticity + a hard BCC phase + a hard Laves phase, which makes the alloy in the cast state have higher strength and hardness, while also maintaining good plasticity.
[0081] With the difference of one element content, there are differences in phase structure of multi-component alloys, which ultimately lead to differences in performance. The present application achieves the best combination of strength-plasticity by adding different Al contents (regulating the content of Al elements) to meet the shearing requirements of papers with different hardness. Its performance maintains the high hardness of existing paper cutter materials, and at the same time has obvious advantages over existing materials in terms of main performance indicators such as yield strength, breaking strength and breaking elongation, and the material is in a cast state and does not require heat treatment, saving a lot of heat treatment costs.
[0082] This application provides useful inspiration on how to control the generated phase by changing the alloy elements, thereby improving and regulating the alloy properties. The preparation method is simple and reliable, the selected elements are non-toxic and easy to obtain, the alloy performance has obvious advantages over medium and low-end paper cutters, and it has good economy and high application value.
[0083] The above is only a preferred implementation of the patent of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the patent of the present invention. These improvements and modifications should also be regarded as the scope of protection of the patent of the present invention.
Claims
1. A high-strength, high-hardness, and plastic multi-component alloy material, characterized in that: Its composition is Al in atomic ratio a Cu b Cr c Fe d Ti e V f , where a:b:c:d:e:f = (0.1-1.1):(0.8-1.2):(0.8-1.2):(0.8-1.2):(0.8-1.2):(0.8-1.2).
2. The high-strength, high-hardness, and plastic multi-component alloy material according to claim 1, characterized in that: The composition of the alloy material is Al in atomic ratio. 0.2 Cu1Cr1Fe1Ti1V1.
3. The high-strength, high-hardness, and plastic multi-component alloy material according to claim 1, characterized in that: The composition of the alloy material is Al in atomic ratio. 0.5 Cu1Cr1Fe1Ti1V1.
4. The high-strength, high-hardness, and plastic multi-component alloy material according to claim 1, characterized in that: The composition of the alloy material is Al1Cu1Cr1Fe1Ti1V1 in atomic ratio.
5. The method for preparing the high-strength, high-hardness and plastic multi-component alloy material according to any one of claims 1 to 4, characterized in that: The method is to place a titanium block and a metal element prepared according to a ratio in a non-consumable vacuum arc melting furnace respectively, and melt the titanium sponge block first under an inert atmosphere; evacuate the furnace, and arc-melt the metal element under an inert atmosphere accompanied by electromagnetic stirring. After the arc melting is completed, the product is refining and the process is repeated for many times to obtain an alloy sample; after removing the oxide layer on the surface of the alloy sample, the alloy sample is melted and cooled to form.
6. The method for preparing a high-strength, high-hardness, and plastic multi-component alloy material according to claim 5, characterized in that: After the metal titanium block and the metal element are prepared, a step of removing impurities and oxides on the surface of the metal element and the metal titanium block is also performed, and the method for removing the oxide layer on the surface of the alloy sample is the same as the method for removing impurities and oxides on the surface of the metal element and the metal titanium block, specifically: using an angle grinder, a grinding wheel machine or sandpaper to grind the metal element, the metal titanium block, and the alloy sample, and then using alcohol or acetone as a cleaning solvent, the metal element, the metal titanium block, and the alloy sample are oscillated and cleaned in an ultrasonic wave for 3-20 minutes; Among them, the power density of ultrasound is 0.5-1.5W / cm 2 , frequency is 20-100Hz.
7. The method for preparing a high-strength, high-hardness, and plastic multi-component alloy material according to claim 5, characterized in that: The specific method of vacuuming is to vacuum to 2.5×10 -3 After reaching 1-20 Pa, inert gas is added to restore the pressure in the furnace to 1-10 Pa.
8. The method for preparing a high-strength, high-hardness, and plastic multi-component alloy material according to claim 5, characterized in that: The arc melting current is 30-150A and the duration is 30-150s.
9. The method for preparing a high-strength, high-hardness, and plastic multi-component alloy material according to claim 5, characterized in that: The molding process is carried out by vacuum suction casting with a pressure of 1-20Pa.
10. Use of the high-strength, high-hardness, and plastic multi-component alloy material according to any one of claims 1 to 4 in the preparation of paper cutters.